Uroptychus minutus Benedict, 1902 and a closely related new species (Crustacea: Anomura: Chirostylidae) from the western Atlantic Ocean - Baba, Keiji; Wicksten, Mary (Zootaxa, 2015)
A new squat lobster, Uroptychus marissae, is described based upon two specimens taken associated with the antipatharian Tanacetipathes sp. from the northern Gulf of Mexico, at a depth of about 90 m. It closely resembles U. minutus Benedict, 1902, known only from the type material from off Trinidad. The original description is so brief that an opportunity is taken here to redescribe it to help discriminate between the two species.